Media Edutainment sebagai Solusi Permasalahan Hasil Belajar Matematika Siswa Sekolah Dasar - Ayu Harlinda; Dwi Cahaya Nurani; Mazda Leva Okta Safitri (Mafa Press in Collaboration with PGMI Tarbiyah Faculty IPMAFA, 2023)
This study aims to examine the effectiveness of using edutainment media in improving student learning outcomes in calculating the surface area of tube shapes at SD Negeri 02 Indralaya Utara. This research used experimental method with One Group Pretest Posttest Design. The sample in this study was class VI A which had a total of 31 students including 20 girls and 11 boys. The data collection technique used was a test. The results showed that there was a significant increase in learning outcomes after using edutainment media. From the calculation results, the average pretest score is 50 while the average posttest score is 80. Based on the hypothesis test, the score zcount = -8.0864 while ztabel = 1.9599 with a level of 0.05 (5%). This shows that zcount < ztabel which means H0 is rejected and H1 is accepted. So it can be concluded that edutainment media can improve student learning outcomes in calculating the surface area of tube shapes at SD Negeri 02 Indralaya Utara. Therefore, edutainment media can be a solution in overcoming the problems of students' math learning outcomes at the basic education level.